2021
DOI: 10.2187/bss.35.15
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of simulated microgravity and radiation on chromosome aberrations in human peripheral blood lymphocytes

Abstract: To u n d e r s t a n d t h e c o m b i n e d e f f e c t o f microgravity (μG) and space radiation on cellsis an important requirement for the anticipated space travel by humans. Cultured cells, such as human fibroblasts and lymphoblasts, were used in previous studies, and we observed changes in the expression of some cell-cycle-related genes and increased chromosome aberrations (CAs) in these cells under simulated μG. In this study, we investigated the combined effect of μG and space radiation on human periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The custom-made 3D clinostat (Portable Microgravity Simulator PMS-CSTI; Advanced Engineering Services Co. Ltd. (AES), Ibaraki, Japan) has been described and characterized by Ikeda et al [ 64 ] and used extensively by our group [ 18 , 19 , 64 , 65 , 66 ]. It is housed in the laboratory of Dr. Akihisa Takahashi, Gunma University Heavy Ion Medical Center, Maebashi, Gunma, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…The custom-made 3D clinostat (Portable Microgravity Simulator PMS-CSTI; Advanced Engineering Services Co. Ltd. (AES), Ibaraki, Japan) has been described and characterized by Ikeda et al [ 64 ] and used extensively by our group [ 18 , 19 , 64 , 65 , 66 ]. It is housed in the laboratory of Dr. Akihisa Takahashi, Gunma University Heavy Ion Medical Center, Maebashi, Gunma, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Since chromosome exchanges, especially translocations, are positively correlated with many cancers [77,78], it is a good biomarker to assess cancer risk for the astronauts. Ground-based studies also showed increased chromosome aberrations with simultaneously exposed to radiation and simulated microgravity [79][80][81].…”
Section: Chromatin Structurementioning
confidence: 98%
“…Space flight conditions differ to those on Earth due to cosmic ionizing radiation (IR) and the absence of gravity, known as microgravity (µG), both of which pose health risk factors to humans, causing complex DNA damage and genome instability [1][2][3][4][5]. It is crucial to gain more insights on these factors, as astronauts will be continuously exposed to them in long-duration exploration missions, such as those to the Moon or Mars, which require humans to remain in space for days, months and even years.…”
Section: Introductionmentioning
confidence: 99%